Análise experimental do cisalhamento em vigas de concreto armado reforçado com microfibras - OLIVEIRA, Mateus Gonçalves de (Universidade Federal do Pará, 2020)
The shear study for small, medium and large works, the latter known as works of art, with the use of reinforced or prestressed concrete presents particularities in the definitions of the traces, since, it has the need to minimize the propagation of fissures, as well as to obtain suitable mixtures considering the high characteristic high diameter of the large aggregates, as well as to avoid deleterious reactions in the concrete. In this sense, the main objective of this research is to analyze the shear behavior of reinforced concrete beams, with reinforcement of glass and polyester microfibers for each type of cited in volumetric fractions (0,024%, 0,032% e 0,048%), comparing them with the behavior of fiber- aiming its application in structural elements. In order to meet the proposal of this research, the methodology was based primarily on the characterization of concrete constituent materials (cement, small and large aggregates and fibers already mentioned), concrete dosage based on the Concrete Dosage method EPUSP -IPT, concrete of the beams, being: one of reference without fiber addition and 6 (six) with additions of microfiber of glass and polyester, being three (three) for each one of them, and later analysis as to shear through the breaking of the experimental beams, and computational analysis between the beam modeled in the Response 200 software considering stirrups throughout its section and the experimental reference without stirrups in 1/3 of its sections. It can be stated that the glass and polyester microfibers have shown that their uses can be used as partial replacement of the transverse reinforcement; contributed to post-peak or post-cracking stability; contributed to the gain in shear strength of 15.1% for VFV01 (beam with addition of glass microfibers with a percentage of 0.024%) and 21.6% of VFP02 (beam with addition of polyester microfiber with a percentage of 0.032%) both in relation to VR (reference beam). Therefore, this study demonstrated that the fibrous reinforcement can be used as control efficiency and as well as shear performance improvement in structural concrete.